Isolation and characterization of actinobacteria from Lake Magadi, Kenya - Ronoh, Regina C.; Budambula, Nancy; Mwirichia, Romano K.; Boga, Hamadi I. (Academic Journals, 2013)
Actinobacteria are ubiquitous and have been detected in terrestrial and aquatic ecosystems. Although, various studies have focused on the ecology of this phylum, data on the ecology of actinobacteria endemic to soda lakes are scanty. This study aimed to determine actinobacterial diversity in Lake Magadi. Four different sampling points were selected randomly within the lake to cover a broad range of sample diversity. Wet sediments and water samples were collected from each sampling point. Good success in isolation of actinobacteria was obtained using a variety of strategies designed to select against fast growing bacteria. Serially diluted samples were plated on growth media containing complex substrates such as malt and chitin. The media was prepared using sterile lake water and pH kept at 8 which is high for most bacteria. DNA was extracted from the isolates and the 16S rRNA genes amplified using primers described to be domain specific for actinobacteria. The isolates were characterized both physiologically and biochemically and were screened for the presence of polyketide synthase-1 genes. The amplified 16S rRNA gene sequences were used for sequence analysis to identify the isolates and establish their phylogeny. Four actinobacteria isolates affiliated with the genera Rhodococcus, Dietzia, Microbacterium and Nocardia were obtained. BLAST analysis showed that all the isolates had between 97 and 99% similarity to their close relatives. Three of the isolates were positive for polyketide synthase genes. These results increase the number of actinobacteria isolates from soda lakes for potential use in biotechnology research.
DOI: 10.5897/AJMR2012.2296
Keywords: Actinobacteria; diversity; 16s rRNA; Lake Magadi